Pengaruh Terapi Murottal Al-Qur’an Surah Ar-Rahman Terhadap Kualitas Tidur Lansia Di Upt Rumah Pelayanan Lanjut Usia Terlantar Budhi Dharma Yogyakarta: The Effect of Surah Ar-Rahman Murottal Al-Qur’an Therapy on Sleep Quality for the Elderly at UPT Budhi Dharma Abandoned Elderly Service House Yogyakarta - Isti Antari; Dwi Nur Anggraeni; Ria Arthica (Journal of Health, 2023)
Background: Poor sleep quality is a disorder that often occurs in the elderly. The impact of sleep disturbances in the elderly is the body's inability to restore its original state so that it causes weakness, headache, drowsiness and fatigue. Handling that can be done to improve sleep quality is with pharmacological and non-pharmacological treatment. One of the non-pharmacological therapies that can be done is Al-Qur'an Murottal Therapy. Research objective: to determine the effect of Al-Qur'an murrotal therapy on sleep quality in the elderly. Research Method: pre-experimental design with a one group pretest-posttest approach, carried out on 1 June 2022 - 7 June 2022 for 15 minutes before going to bed. The population is 20 elderly. The sample in this study were 20 respondents who experienced sleep disturbances using the total sampling technique. The measuring tool uses the PSQI questionnaire and speakers. The speaker contains the surah Ar-Rahman which was read by Qori Misyari Rasyid and the speakers are playing at 75 decibels. Results and discussion: there is an influence on the sleep quality of the elderly after listening to Murottal Al-Qur'an surah Ar-Rahman with a ρ value of .000. Conclusion: Al-Qur'an murrottal therapy can improve sleep quality in the elderly and research needs to be carried out using other non-pharmacological therapies to improve sleep quality in the elderly.